The role of psychology in the prevention and fight against terrorism and in dealing with the consequences of terrorism - Sotiroska Ivanoska, Kalina (MINISTRY OF DEFENCE REPUBLIC OF NORTH MACEDONIA, 2021)
This article discusses the benefits of using the knowledge and tools of psychology in counter-terrorism, which can contribute to maintaining security and defense nationally and internationally. A number of contemporary psychological strategies, such as increasing the awareness of the general population, using methods and techniques for staff selection, offering psychological support and training, as well as increasing the resilience of individuals can provide typical and proven psychological solutions in the fight against terrorism. The problems and challenges faced by cyber security employees, as well as the possible psychological response to such challenges are briefly discussed. It can be concluded that the greater the range of psychological interventions that will be used in repairing the psychological consequences of terrorism, the greater the benefit for the whole community, and not only for those directly involved in the terrorist act.
Keywords: psychology, counter-terrorism, psychological strategies